How women with obsessive compulsive disorder experience maternity care and mental health care during pregnancy and postpartum: A systematic literature review - Burton, HAL; Pickenhan, L; Carson, C; Salkovskis, P; Alderdice, F (Elsevier, 2022)
Introduction Obsessive Compulsive Disorder has a higher prevalence in pregnancy and postpartum than in the general population. Experiences of maternity care and mental health care can impact the health and wellbeing of perinatal women. The aim of this review was to synthesize evidence on the experiences of maternity care and mental health care for women with OCD during pregnancy and postpartum.